The function of histone lysine methylation related SET domain group proteins in plants. (19th March 2020) - Zhou, Huiyan; Liu, Yanhong; Liang, Yuwei; Zhou, Dong; Li, Shuifeng; Lin, Sue; Dong, Heng; Huang, Li
Abstract: Histone methylation, which is mediated by the histone lysine (K) methyltransferases (HKMTases), is a mechanism associated with many pathways in eukaryotes. Most HKMTases have a conserved SET (Su(var) 3‐9, E(z), Trithorax) domain, while the HKMTases with SET domains are called the SET domain group (SDG) proteins. In plants, only SDG proteins can work as HKMTases. In this review, we introduced the classification of SDG family proteins in plants and the structural characteristics of each subfamily, surmise the functions of SDG family members in plant growth and development processes, including pollen and female gametophyte development, flowering, plant morphology and the responses to stresses. This review will help researchers better understand the SDG proteins and histone methylation in plants and lay a basic foundation for further studies on SDG proteins.